Propuesta de vivienda sostenible que considere la identidad local en las parroquias rurales de Licán y Calpi del cantón Riobamba - Vaca Barahona, Bryan Rogelio (2023)
The main objective of the research was to establish a sustainable housing proposal based on the study of heritage housing in comparison with current housing for the parishes of Licán and Calpi, canton Riobamba, province of Chimborazo. The research has an exploratory, descriptive scope due to its partly unknown nature, as it describes typologies and architectural design. We talk about qualitative variables, the same that once obtained based on information surveys in the field, as by management in the GADMR were processed and tabulated to classify with the help of a spreadsheet and based on the typologies present in the sector; the result was 29 houses of adobe and wood masonry, 11 of mud and wood, 8 of stone and 5 with a porticoed structure whose characteristics offer advantages and disadvantages compared to each other. With all the processes carried out, a housing proposal is generated, satisfying the needs of a typical family from the sector, taking into account a correct structural design considering previous knowledge and indications and restrictions of the current regulations, as well as preserving the identity, customs, way of life and tradition of the parishes, seeking to generate comfort and functionality within the houses, while trying to make it as ecological as possible through the use of renewable materials such as wood and elements of low environmental impact such as prefabricated walls